What did I forget to do in this question? What should the answer be?
Use only Quadratic Formula

[tex] {7x}^{2} + 9x + 2 = 0[/tex]
[tex] {x}^{2} + 9x + 14 = 0[/tex]
[tex](x + 7)(x + 2) = 0[/tex]
x= -7,x=-2​

Respuesta :

The mistake is in the first step. You seem to want to divide through by 7, but you only did it correctly with the x ² term. What you should have after doing this is

7x ² + 9x + 2 = 0

→   x ² + 9/7 x + 2/7 = 0

This step isn't actually necessary to begin with since the starting quadratic is easily factorized:

7x ² + 9x + 2 = (7x + 2) (x + 1) = 0

Then

7x + 2 = 0   or   x + 1 = 0

7x = -2   or   x = -1

x = -2/7   or   x = -1